Research on Static Triaxial Mechanical Properties of New CementSoil Reinforced with Polypropylene Fiber - Qiang Wang; Rui Tang; Qun Cheng; Xiankun Wang; Fang-ling Liu (Advances in Materials Science and Engineering)
Through the laboratory test, the mechanical properties of cementsoil with adding desulfurization gypsum, fly ash, and polypropylene fiber were studied. Three different percentages (0%, 0.5%, and 1.0%) of polypropylene fiber were mixed into new cementsoil for which the cement content is 15% of the dry soil weight, the desulfurization gypsum content is 2% of the dry soil weight, and the fly ash content is 1.0% of the dry soil weight. The new cementsoil strength reinforced with polypropylene fiber was studied by triaxial test under different polypropylene fiber mixing ratio, different age, and different confining pressure. The experimental results show that, compared with ordinary soil, the deviatoric stress and the peak shear strength reinforced with polypropylene fiber have different amplitude increase. At the same time, the internal friction angle of new cementsoil with polypropylene fiber increases slightly with the growth of the age. The stress-strain curve of the polypropylene fiber cementsoil has the typical work hardening characteristic and has the characteristics of bulge fracture.